The Relationship between Green Purchase and Purchase Intention among Generation Z in Malaysia - Yiaw Xin Yue,; Norasmiha Mohd Nor, (Research in Management of Technology and Business, 2024)
Green products are specifically crafted to safeguard or enhance the environment through actions such as conserving energy and resources, as well as minimizing or eliminating the generation of toxic waste, pollution, and the utilization of harmful substances. In Malaysia, major companies have launched their green programs to demonstrate their commitment to environmental sustainability. The individual consuming ability has substantially increased as the economy and industrial development have grown rapidly, leading to greater damage to the environment. There is still a knowledge gap between environmental concerns and Malaysians. The majority of educated young consumers still have a lack of understanding of green products. Therefore, the objective of this study is to identify the level of green purchase intention and to investigate the relationship between environmental knowledge, environmental concern, and perceived consumer effectiveness on green purchase intention among Generation Z in Malaysia. This study adopts quantitative research, and the data was collected using a non-probability sampling approach. A sample of 350 respondents was used to answer the questionnaire and all the data were analyzed through SPSS software. The researcher adopted descriptive analysis and inferential analysis in the process of data analysis. The outcome indicated that most factors attained a moderate mean score based on the central tendency level. The results of the correlation analysis showed that all the independent variables were positively correlated with green purchase intention. The research findings conclude that environmental concern had the strongest relationship with green purchase intention among the three factors.